The Strategy of Internalizing Character Values through Distance Learning from the Perspective of Prospective Teachers - Syihabuddin, Syihabuddin; Khalid, Shofa Musthofa (Universitas Islam Negeri Raden Intan Lampung, 2022)
The Covid-19 pandemic had brought significant impacts on many aspects of life, including in the education sector in which learning activities have to be held online. In one hand, there are numerous benefits of online learning, but it also raises drawbacks on the other hand. One of the flaws is the lack of character values that teachers can instill through distance learning. Thus, the purpose of this research is to address the shortcomings of online learning by focusing on four issues: the types of character values internalized to students, the strategies used by teachers to internalize values, the evaluation of value internalization activities, and the obstacles faced by teachers when cultivating character values. The researcher employs a descriptive narrative inquiry method to investigate these four issues. In-depth interviews are conducted with 17 outstanding teachers from West Java Province. Data analysis reveals that teachers apply 30 strategies to internalize 17 values based on 15 principles. Internalization materials, methods, and principles are typically drawn from religion, philosophy, and culture. Teachers face challenges in internalizing values, particularly in the terms of network connection, finances, tool reliability, and lack of communication skills.